A STUDY ON THE REAL MADRID FOOTBALL TEAM'S FULL-BACKS' INVOLVEMENT IN THE ATTACK - Péter GUCSI VÉGH; János TÓTH JR; János TÓTH (Cluj University Press, 2016)
Real Madrid is one of the best teams in the world. This study examines the team's game system and the full-backs' involvement in the attack based on a video analysis. How effectively they enter the attack, what passes they complete in the different parts of the pitch (attacking, middle, defensive third) and how they help the team's attacks. I analyzed in the flat back four game scheme the importance of the full-backs and their participation in the attack. I examined the matches of the first ten round in the 2015/2016 season, with special emphasis on the efficiency of the full-backs' entry into the attack. In each match the team's line-up was characterized by the flat back four game scheme. I prepared a graph for each match which shows what passes were completed by the full-backs and how successful they were. The results of the analyzed matches (n = 10) reveal that out of the total number of passes (1239) 597, that is 48%, were forward passes which aimed at helping the attack. 587 times the passes were completed by the full-backs and 461 times they were successful which equals to a pass accuracy of 77%. 32% of the passes took place in the attacking third, whereas in the middle third 52% and in the defensive third only 16% of the passes occurred. This study also addresses in details the passing efficiency. Another method that I used in the study is the heatmap. It is a special chart pointing out that throughout the whole match up to what degree took the full-back part in the game in the different parts of the pitch and where he was the most active. The graph shows only the two full-backs' play which makes it very easy to analyze which parts of the football pitch were they the most active. The figures reveal the number of the ball contacts in the examined matches and based on this it is obvious that the left full-back was much more active during the matches. Without doubt it can be said that in Real Madrid team the left full-back helps the attacks in an almost midfielder manner. The arrows located on the heatmap indicate the direction of the team's attack, helping the analysis of the graph.